Relational Governance Innovation Sustains Sugarcane Smallholder Partnerships in East Java: Inovasi Tata Kelola Relasional Mempertahankan Kemitraan Petani Tebu Skala Kecil di Jawa Timur - Rafish Rafish; Ika Sari Tondang; Dona Wahyuning Laily (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Sugarcane is a strategic commodity requiring continuous raw material supply from agricultural producers to maintain national sugar industry operations. Specific Background Sugar factories heavily rely on plasma suppliers, necessitating robust institutional programs to ensure supply certainty, mitigate business risks, and align mutual interests. Knowledge Gap While previous literature independently correlates service quality or technical assistance with relationship continuity, simultaneous evaluations of behavioral and operational predictors within entirely supplier-dependent factories remain limited. Aims This study investigates how plasma supplier satisfaction, confidence, and perceived organizational backing concurrently predict the sustainability of institutional programs at PG Gempolkrep. Results Utilizing a quantitative explanatory design with a purposive sample of 90 active sugarcane suppliers, Partial Least Squares-Structural Equation Modeling reveals that the model explains 61.0 percent of the variance in program continuity. Furthermore, satisfaction, confidence, and organizational backing all demonstrate positive and significant correlations with sustainability, identifying confidence as the most dominant structural predictor. Novelty This research expands the commitment-trust theory by simultaneously quantifying the structural dominance of relational integrity over instrumental assistance in agribusiness alliances. Implications Agribusiness managers must prioritize transparent communication, operational honesty, and consistent policy execution over mere technical provision to secure long-term raw material supply and cultivate enduring supplier alliances. Highlights Transparent communication and consistent corporate policies fundamentally secure long-term agribusiness agreements. Plasma grower confidence structurally dominates over operational assistance in maintaining supply relationships. Fulfilling agricultural service expectations guarantees the long-term viability of sugar industry programs. Keywords: Company Support, Plasma Growers, Relational Trust, Agribusiness Sustainability, Structural Equation Modeling